(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nifuratel, Albendazol and Metronidazol were used in the second step (intervention on parasite and it’s elimination from the host) of 3-step therapy of lambliasis at 125 children.